2018
DOI: 10.1016/j.ejphar.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of 5-aminolevulinic acid induces heme oxygenase-1 expression in peripheral blood mononuclear cells of healthy human subjects in combination with ferrous iron

Abstract: Heme oxygenase-1 (HO-1) is a major anti-inflammatory enzyme and a key regulator that induces immune tolerance through affecting the differentiation of dendritic cells. The aim of this study is to determine whether the combination of 5-aminolevulinic acid (ALA) and iron induces HO-1 expression in healthy human peripheral blood mononuclear cells (PBMC). The study was an open labeled, non-randomized, non-placebo-controlled trial using healthy male adults and consisted of three parts. Study A aimed to find the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…At 24 hpi (Figure 5e), ALA15 and ALA60 showed increase in HO-1 expression levels, although not significant. Increase in HO-1 gene expression levels after 5-ALA supplementation was reported previously (Nishio et al, 2014;: Ito et al, 2018). To date, the role of HO-1 in shrimp immunity is not known.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…At 24 hpi (Figure 5e), ALA15 and ALA60 showed increase in HO-1 expression levels, although not significant. Increase in HO-1 gene expression levels after 5-ALA supplementation was reported previously (Nishio et al, 2014;: Ito et al, 2018). To date, the role of HO-1 in shrimp immunity is not known.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies of vertebrates and vertebrate cell lines support the hypothesis that exogenous 5‐ALA enhances haem synthesis and activity of haemoproteins: 5‐ALA administration (a) increased intracellular haem levels, increasing the activity of cytochrome P450 in vitro (Miura et al., ); (b) increased the activity of cytochrome c oxidase of the electron transport chain and raised ATP levels in mouse liver (Ogura et al., ); (c) enhanced protein expression of mitochondrial complexes III–V in mouse adipose tissue (Ota et al., ); (d) induced REV‐ERBα expression (Yamashita et al., ); and (e) induced both protein and mRNA expression of haem oxygenase‐1 (HO‐1) (a rate‐limiting enzyme in haem degradation) (Nishio et al., : Ito et al., ). 5‐aminolevulinic acid was also reported to enhance the immune response in chickens (Sato et al., ) and pigs (Chen et al., ) and improves growth performance in eels (Yasumoto, Miyanari, Yoshimura, Kondo & Takahashi, ) (although there is some disagreement on the effect of 5‐ALA on growth; see below).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We previously reported that ALA/SFC enhances HO-1 expression, which has anti-inflammatory and antioxidant activities, in a mouse fatty liver model, and in peripheral blood mononuclear cells of healthy humans 6,8 . We therefore carried out western blot analysis and quantitative reverse transcription PCR of the HO-1 gene.…”
Section: Resultsmentioning
confidence: 98%
“…We previously reported that ALA supplementation in mice enhances cytochrome c oxidase (COX) activity and ATP production levels in liver, and ALA combined with sodium ferrous citrate (SFC) administration upregulates the expression of OXPHOS complexes III, IV, and V in white adipose tissues of diet-induced obese mice, resulting in reduced lipid content of adipocytes 4,5 . Furthermore, ALA combined with SFC in healthy humans increased the expression levels of haem oxygenase-1 (HO-1) in peripheral blood mononuclear cells, which has cytoprotective effects against oxidative stress and inflammation 6,7 .
Figure 1Haem biosynthesis pathway. Haem is biosynthesised via several steps in the cytoplasm and mitochondria.
…”
Section: Introductionmentioning
confidence: 99%